Challenges Confronting Social Service Professionals in Shelters Assisting People Experiencing Homelessness in Johannesburg, South Africa - Chauke, Ntokozo Shaun; Khumalo, Gift (International Journal on Homelessness, 2026)
An estimated 150 million people are homeless worldwide, with homelessness being poorly documented and not prioritized in policymaking. In South Africa, over 200,000 people are estimated to be homeless, whilst the official figure sits at 55,719. Prior research has highlighted the causes and effects of homelessness, focusing on the experiences of people experiencing homelessness. However, there has been a lack of research on the experiences of service providers in the sector. Thus, this study examined the experiences of social services staff regarding the challenges they encountered while providing services to individuals experiencing homelessness in Johannesburg. A qualitative approach and descriptive single case study design were utilized. Purposive sampling was employed to recruit 12 social services staff from two shelters, and data were collected through semi-structured interviews. Reflexive thematic analysis revealed that the staff faced various challenges related to interactions with people experiencing homelessness, their employer organisation, external organisations, and outreach initiatives, as well as adverse effects arising from these challenges. These findings resonate with local and global literature, adding nuance to already recognized challenges related to clients and organisations, while also offering novelty, particularly regarding external organisations and outreach initiatives in the homeless sector. Furthermore, the findings highlight the persistent need for debriefing, supervision, and training workshops to ensure the effectiveness of shelter staff in the homeless sector, and for including shelter management in similar research to gather more details on organisational limitations and a lack of management support.